Effects of Bifidobacterium on metabolic parameters in overweight or obesity adults: a systematic review and meta-analysis - Huang, Junmei; Cheng, Hao (Frontiers in Microbiology, 2025)
ObjectiveThis study endeavors to elucidate how Bifidobacteria supplementation affects metabolic parameters among overweight or obese populations.MethodsA systematic review and meta-analysis were carried out leveraging PubMed, Embase, Cochrane Library, and Web of Science. Merely randomized controlled trials (RCTs) were included.Results21 RCTs were encompassed for our final analysis. Bifidobacteria supplementation was effective in weight management for overweight or obese patients. The experimental group receiving Bifidobacteria exhibited a marked decrease in weight (WMD: −0.607 kg; 95% CI: −0.910, −0.303, I2 = 11.9%) and BMI (WMD: −0.214 kg/m2; 95% CI: −0.259, −0.169, I2 = 4.1%) in contrast to the control, although the significant effect was not noted on WC. Moreover, while Bifidobacteria supplementation led to no marked drop in FBG or HbA1c, it improved the insulin (SMD: -0.268; 95% CI: −0.470, −0.066, I2 = 5.4%). However, there were no evident variations in TC, TG, HDL-C, or LDL-C across groups.ConclusionOur study findings confirmed that Bifidobacteria contributes to a slight reduction in weight and BMI among the overweight or obese populations, making it a potential adjunctive approach for weight management. Furthermore, it may help regulate insulin levels, though its impact on hyperglycemia and hyperlipidemia remains limited.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO. Registration No. CRD42025635324.